New Open-Source Tools: Using Bonsai for Behavioral Tracking and Closed-Loop Experiments - Lopes, Gonçalo; Monteiro, Patricia (Frontiers in Behavioral Neuroscience, 2021)
Being able to dynamically control a behavioral task based on real time animal behavior is an important feature for experimental neuroscientists. But designing automated boxes for behavioral studies requires a coordinated combination of mechanical, electronic, and software design skills which can challenge even the best engineers, and for that reason used to be out of reach for the majority of experimental neurobiology and behavioral pharmacology researchers. However, due to parallel advances in open-source hardware and software developed for neuroscience researchers, by neuroscience researchers, the landscape has changed significantly. Bonsai is an open-source visual programming framework that allows acquisition, control and online processing of many different data streams, enabling easy prototyping of complex experimental designs in neuroscience. This approach makes it easy for researchers, without programming skills, to combine the operation of several devices in parallel and design their own integrated custom solutions, turning behavioral neuroscience more accessible than ever before. Here we demonstrate some practical examples and tutorials using Bonsai to design simple neuroscience experiments and help researchers to immediately get started, including video tracking of behavior and closed-loop electrophysiology.